2003
DOI: 10.1074/jbc.m209883200
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonicity Activates Na+/H+ Exchange through Janus Kinase 2 and Calmodulin

Abstract: The type 1 sodium-hydrogen exchanger (NHE-1) is a ubiquitous electroneutral membrane transporter that is activated by hypertonicity in many cells. NHE-1 may be an important pathway for Na ؉ entry during volume restoration, yet the molecular mechanisms underlying the osmotic regulation of NHE-1 are poorly understood. In the present study we conducted a screen for important signaling molecules that could be involved in hypertonicity-induced activation of NHE-1 in CHO-K1 cells. Hypertonicity rapidly activated NHE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 47 publications
4
74
0
Order By: Relevance
“…A schematic diagram for the ionic pathways identified from the CHO cells are shown in Fig. 1 [25][26][27][28][29][30]. The sensor chip allows us to repeatedly expose cultured cells to mercurials and other reagents and to follow the response in real time.…”
Section: Introductionmentioning
confidence: 99%
“…A schematic diagram for the ionic pathways identified from the CHO cells are shown in Fig. 1 [25][26][27][28][29][30]. The sensor chip allows us to repeatedly expose cultured cells to mercurials and other reagents and to follow the response in real time.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with its reduction in the intracellular alkalinization, calmidazolium reduced the hypertonicityinduced proton secretion rate by 15% in the trout cells (Fig.·7B). This is considerably less than the 55 to 94% inhibition of hypertonicity-induced proton secretion seen in CHO-K1 cells exposed to various CaM inhibitors (Garnovskaya et al, 2003b). Compared with the severe reduction in alkalinization, indicating that a significant amount of protons remained in the cytoplasm during hypertonic stress in the presence of calmidazolium, the reduction in the rate of proton secretion was smaller than might be expected.…”
Section: Removal Of Intracellular Camentioning
confidence: 59%
“…Ca 2+ -calmodulin (CaM) has been shown to be involved in the activation process of NHE-1 in response to a variety of stimuli including mitogenic factors, ionomycin and serotonin (Wakabayashi et al, 1994;Bertrand et al, 1994;Garnovskaya et al, 2003a), and, importantly, osmotic shrinkage (Dascalu et al, 1992;Shrode et al, 1995;Shrode et al, 1997;Garnovskaya et al, 2003b). Consistent with the latter studies, our data confirmed an important role of a CaMdependent pathway in the hypertonicity-induced NHE-1 activation in trout hepatocytes, as the inhibition of CaM by calmidazolium reduced the hypertonicity-induced pHi increase by 54% (Fig.·7A).…”
Section: Removal Of Intracellular Camentioning
confidence: 99%
“…One tyrosine kinase activated by decreased cell volume is Janus kinase 2 (Jak2) (Gatsios et al, 1998). Jak2 has been found to be required for full activation of NHE1 by decreased cell volume in Chinese Hamster Ovary (CHO) cells, where Jak2 activates NHE1 through phosphorylating and activating Calmodulin (CaM), which then binds to and activates NHE1 (Garnovskaya et al, 2003). This mechanism also appears to operate in mouse preimplantation embryos, where activation and tyrosine phosphorylation of Jak2 is markedly increased upon a cell volume decrease, and expression of a dominant negative Jak2 or pharmacological Jak2 or CaM inhibitors block NHE1 activation (Zhou and Baltz, 2012).…”
Section: Acute Cell Volume Regulation By Inorganic Ion Transport In Ementioning
confidence: 99%